'Detachment' of icefield outlet glaciers: catastrophic thinning and retreat of the Columbia Glacier (Canada). Issue 2 (29th November 2019) - Rippin, David M.; Sharp, Martin; Van Wychen, Wesley; Zubot, Darryl
ABSTRACT: We present an investigation of changes taking place on the Columbia Glacier, a lake‐terminating outlet of the Columbia Icefield in the Canadian Rockies. The Columbia Icefield is the largest, and one of the most important, ice bodies in the Canadian Rockies. Like other ice masses, it stores water as snow and ice during the winter and releases it during warmer summer months, sustaining river flows and the ecosystems that rely on them. However, the Columbia Glacier and Icefield is shrinking. We use Landsat and Sentinel‐2 imagery to show that the Columbia Glacier has retreated increasingly rapidly in recent years, and suggest that this looks set to continue. Importantly, we identify a previously undocumented process that appears to be playing an important role in the retreat of this glacier. This process involves the ' detachment ' of the glacier tongue from its accumulation area in the Columbia Icefield. This process is important because the tongue is cut off from the accumulation area and there is no replenishment of ice that melts in the glacier's ablation area by flow from upglacier. As a consequence, for a given rate of ablation, the ice in the tongue will disappear much faster than it would if the local mass loss by melting/calving was partly offset by mass input by glacier flow. Such a change would alter the relationship between rates of surface melting and rates of glacier frontal retreat. We provide evidence that detachment has already occurred elsewhere on the Columbia Icefield and that it is likely to affect other outlet glaciers in the future. Modelling studies forecast this detachment activity, which ultimately results in a smaller 'perched' icefield without active outlets. © 2019 John Wiley & Sons, Ltd. Abstract : Rapid retreat of the Columbia Glacier is (in part) attributed to the detachment of this outlet glacier from the Columbia Icefield. Such 'detachment' has occurred previously on other outlet glaciers of the Columbia Icefield and looks set to take place on more. We identify this process of 'detachment' (whereby outlet glaciers losecontact with the upper icefield) as an important mechanism by which icefields may decay. 'Detachment' resultsin an isolated 'perched' icefield, accelerated glacier retreat and snout‐stagnation.